Explorations into modernity, colonialism and genocide: Revisiting the past in the present - Henning Melber (Acta Academica, 2017)
This essay contextualises forms of mass violence and genocide in a historical perspective since the era of enlightenment. Western modernity and its notion of civilisation domesticated and colonised at home and abroad. The concept of development imposed during the colonial era elsewhere too included organised violence as an integral part of the expansion into the rest of the world. Since then violence remains an element of the project of globalisation. It has also infected those in the former so-called periphery executing control over people. Forms of domination anchored in a colonial mindset are not any longer only of Eurocentric or European brand but alive in certain forms of power executed elsewhere too. Hence there remains a global responsibility to decolonise the mind.